Asymmetric Nonfullerene Small Molecule Acceptors for Organic Solar Cells. Issue 25 (13th May 2019) - Li, Chao; Fu, Huiting; Xia, Tian; Sun, Yanming
Abstract: Symmetry breaking provides a new material design strategy for nonfullerene small molecule acceptors (SMAs). The past 10 years have witnessed significant advances in asymmetric nonfullerene SMAs in organic solar cells (OSCs) with power conversion efficiency (PCE) increasing from ≈1% to ≈14%. In this review, the progress of asymmetric nonfullerene SMAs, including early reports of asymmetric nonfullerene SMAs, asymmetric PDI‐based nonfullerene SMAs, and asymmetric acceptor–donor–acceptor (A–D–A)‐type nonfullerene SMAs, is summarized. The structure–property relationships and the perspectives for future development of asymmetric nonfullerene SMAs are also discussed. Abstract : Symmetry breaking provides a new material design strategy for nonfullerene small molecule acceptors (SMAs) . The past 10 years have witnessed significant advances in asymmetric nonfullerene SMAs in organic solar cells (OSCs). In this review, the progress of asymmetric nonfullerene SMAs is reviewed. The structure–property relationships and the perspectives for future development of asymmetric non‐fullerene SMAs are also discussed.